Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/tid.13286
|View full text |Cite
|
Sign up to set email alerts
|

Threatening drug‐drug interaction in a kidney transplant patient with coronavirus disease 2019 (COVID‐19)

Abstract: During the novel coronavirus pandemic, organ transplant recipients represent a frail susceptible category due to longterm immunosuppressive therapy. For this reason, clinical manifestations may differ from general population and different treatment approaches may be needed. We present the case of a 36-year-old kidney transplanted woman affected by Senior-Loken syndrome diagnosed with COVID-19 pneumonia after a contact with her positive mother.Initial symptoms were fatigue, dry cough and coryza; she never had f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 11 publications
3
58
0
2
Order By: Relevance
“…14 So far, however, only a few cases of COVID-19 have been reported in KT patients. [3][4][5] The patient we discuss presented overall clinical characteristics similar to those reported in non-transplanted COVID-19 patients. 14 Respiratory data on admission to the ICU were similar to non-immunosuppressed patients.…”
Section: Discussionsupporting
confidence: 57%
“…14 So far, however, only a few cases of COVID-19 have been reported in KT patients. [3][4][5] The patient we discuss presented overall clinical characteristics similar to those reported in non-transplanted COVID-19 patients. 14 Respiratory data on admission to the ICU were similar to non-immunosuppressed patients.…”
Section: Discussionsupporting
confidence: 57%
“…Although renal dysfunction as reflected by decreased eGFR or increased serum levels of creatinine was not considered in the published reports as a co-morbidity, it is important to recognize that renal dysfunction of kidney transplant recipients with COVID-19 ought to be recognized as such. Nevertheless, numerous reports that we reviewed showed that patients with a decreased eGFR plus other comorbidities 39 , 41 , 43 , 44 , 47 , 48 , 52 , 55 or increased serum levels of creatinine plus other comorbidities 36 , 38 , 40 , 42 , 46 , 53 , 54 still achieved a positive outcome. Interestingly, Sharma et al recently completed a retrospective study in which they compared the clinical outcomes of COVID-19 between solid organ transplant recipients and matched nontransplant patients in their medical center, and they found the need for renal replacement therapy in the organ recipients did not affect the incidence of severe COVID-19 and the rate of short-term death 70 .…”
Section: Discussionmentioning
confidence: 91%
“…Fourteen articles were included in the analysis of KT patients with COVID-19. Among these, six were case reports/case series (22)(23)(24)(25)(26)(27), five were correspondences (10,(28)(29)(30)(31), one was a guideline (32), one an editorial (33), and one was a case series on SOT (7). Twenty-three KT cases were described.…”
Section: Kidney Transplant Patientsmentioning
confidence: 99%